A negative electrode-free sodium-based dual-ion battery positive electrode and a preparation method thereof, and a negative electrode-free sodium-based dual-ion battery comprising the positive electrode
By adopting mixtures of embedded yin ions and poverty -sodium ion ion ion orthophyllum materials in the bi -balm -based sodium -based double -ion battery, combined with conductive agents and adhesives to prepare positive pole tablets to solve the problem of low sodium metal accumulation and battery performance, realize the realization High -efficiency energy use and long cycle life.
Patent Information
- Application Number
- CN202410570975.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-09
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-05-09
AI Technical Summary
In the negative-electrode sodium-based dual-ion battery, due to the low efficiency of anion-embedded positive electrode Coulon, the charging energy utilization rate is low. The sodium metal is deposited during the charging process and cannot be completely oxidized during the discharge process, resulting in excessive sodium metal accumulation on the negative current collector. , causing battery short circuit and safety problems, and low cycle life.
65-75%embedded the a positive pole of the yin ions, 15-5%of the poverty-poverty sodium material, 10%conductive and 10%adhesive to prepare the slurry through grinding and solvents, and evenly applied it to the streaming body. In the vacuum drying, prepare the positive electrode of the bilateral bilateral battery of the balm -free bilateral.
Effectively improve or even eliminate the accumulation of negative sodium metal poles, improve the energy efficiency, cycle life and safety of battery, significantly improve the efficiency and capacity of Kuron.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery energy storage, and in particular relates to a cathode-free sodium-based dual-ion battery cathode and a preparation method and application thereof.
[0002] This invention belongs to the 1.3.4 high-end energy storage device materials and devices under the key direction of the 1.3.3.4.1 new generation information technology industry in the catalog of strategic emerging industries. Positive electrode materials include olivine-type phosphates and other lithium-rich materials (such as lithium iron phosphate, etc.), spinel-type lithium manganese oxide materials, layered materials (such as nickel-cobalt-aluminum and nickel-cobalt-manganese, etc.) and their mixed materials. Background Art
[0003] Lithium-ion batteries are widely used due to their high energy density and high cycle stability. However, the abundance of lithium in the earth's crust is low and its distribution is uneven. At the same time, my country is the world's largest importer of lithium resources. Therefore, it is imperative to develop a low-cost, high-energy-density battery system.
[0004] As a new type of electrochemical energy storage structure, dual-ion batteries store energy in synergistically with two ions. Thanks to their special working mechanism, dual-ion batteries have the advantages of good safety, low production and environmental costs, and easy recycling of waste batteries. Considering the advantages of sodium resources such as low cost and abundant resources, Na + Sodium-based dual-ion batteries as charge carriers have received increasing attention in recent years.
[0005] The sodium-based dual-ion battery without negative electrode active materials is constructed. Only aluminum current collector is used as the negative electrode during the assembly process, which simplifies the battery assembly process, thus effectively improving the energy density of the battery system and reducing the battery cost. However, in the sodium-based dual-ion battery without negative electrode, since the coulombic efficiency of the anion-embedded positive electrode is usually low, in addition to the low charging energy utilization rate, the sodium metal deposited on the current collector during the charging process cannot be completely oxidized and converted into Na+ during the discharge process. + Dissolving in the electrolyte causes excessive sodium metal to accumulate on the negative electrode current collector, causing battery short circuits and even safety issues, resulting in a low cycle life. Summary of the invention
[0006] In view of the above problems existing in the prior art, the present invention provides a cathode for a sodium-based dual-ion battery without a negative electrode and a preparation method and application thereof.
[0007] The object of the present invention is achieved in the following manner:
[0008] A negative electrode-free sodium-based dual-ion battery positive electrode comprises, by weight percentage, 65-75% of anion-embedded positive electrode, 15-5% of cation-embedded sodium-poor positive electrode material, 10% of conductive agent and 10% of binder.
[0009] The anion-embedded positive electrode is one of graphite and polytriphenylamine; the cation-embedded sodium-poor positive electrode material is one of sodium titanium phosphate and perylenetetracarboxylic dianhydride (PTCDA); the conductive agent is conductive carbon black (Super-p); and the binder is polyvinylidene fluoride (PVDF).
[0010] A method for preparing a positive electrode of a sodium-based dual-ion battery without a negative electrode, the specific preparation steps comprising:
[0011] S1, grinding the above-mentioned negative electrode-free sodium-based dual-ion battery positive electrode material for 1-2 h, and then preparing a slurry with a solvent of N-methylpyrrolidone (NMP), and the slurry viscosity is 3000-5000 cps;
[0012] S2, uniformly coating the above slurry on the current collector with a surface loading of ≥8 mg / cm2, and vacuum drying at 60-120 °C for 12-36 h.
[0013] A negative electrode-free sodium-based dual-ion battery comprises the positive electrode of the negative electrode-free sodium-based dual-ion battery.
[0014] The negative electrode-free sodium-based dual-ion battery has no negative electrode, which means that the negative electrode has only a current collector but no active material, and the negative electrode current collector is a carbon-coated aluminum foil.
[0015] Compared with the prior art, the present invention utilizes the sodium-poor positive electrode material to discharge and embed Na + The working principle of the invention can effectively improve or even eliminate the accumulation of sodium metal negative electrode, and improve the energy efficiency, cycle life and safety of the battery. In addition, the invention uses a mixture of anion-embedded positive electrode and sodium-poor positive electrode material as the active material, and combines a binder and a conductive agent to prepare the positive electrode sheet. The positive electrode preparation process has good controllability and low cost, and has the potential for large-scale production and application.
[0016] Applying the above-mentioned positive electrode to a negative electrode-free sodium-based dual-ion battery will result in a negative electrode-free sodium-based dual-ion battery with good cycle stability and safety, which will be beneficial to promoting the research progress of dual-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Scanning electron microscope images of the carbon-coated aluminum foil current collector negative electrode before cycling (a) and after the first cycle of Example 1 (b).
[0018] Figure 2 The first cycle charge and discharge curve of Example 1.
[0019] Figure 3 Example 2: Cycle stability test diagram of negative electrode-free sodium-based dual-ion battery.
[0020] Figure 4The first cycle charge and discharge curve of Example 3.
[0021] Figure 5 The first cycle charge and discharge curve of Example 4.
[0022] Figure 6 Scanning electron microscope image of the carbon-coated aluminum foil current collector negative electrode after the first cycle of Comparative Example 1.
[0023] Figure 7 Comparative Example 1 first cycle charge and discharge curve.
[0024] Figure 8 Comparative Example 2: Cycle stability test diagram of sodium-based dual-ion battery without negative electrode. DETAILED DESCRIPTION
[0025] The present invention is further described in detail below in conjunction with specific embodiments so that the purpose, features and advantages of the present invention can be more clearly understood. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict. However, the protection scope of the present invention is not limited by the specific embodiments disclosed below. All other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present invention.
[0026] First of all, it should be noted that "no negative electrode" is an industry term. In layman's terms, a negative electrode-free dual-ion battery means that no negative electrode active materials are added during the production and manufacturing process, and only the negative electrode current collector is used as the nominal negative electrode. However, this negative electrode current collector does not have the function of a negative electrode. Only after the first charge is completed, the metal cations in the electrolyte migrate to the surface of the negative electrode current collector, and the metal layer formed on the negative electrode current collector is the real negative electrode. Or we can understand no negative electrode as no negative electrode during the production and manufacturing process, and the negative electrode appears after the battery is assembled and charged for the first time.
[0027] A negative electrode-free sodium-based dual-ion battery positive electrode comprises, by weight percentage, 65-75% of anion-embedded positive electrode, 15-5% of cation-embedded sodium-poor positive electrode material, 10% of conductive agent and 10% of binder.
[0028] The anion-embedded positive electrode is one of graphite and polytriphenylamine; the cation-embedded sodium-poor positive electrode material is one of sodium titanium phosphate and perylenetetracarboxylic dianhydride (PTCDA); the conductive agent is conductive carbon black (Super-p); and the binder is polyvinylidene fluoride (PVDF).
[0029] A method for preparing a positive electrode of a sodium-based dual-ion battery without a negative electrode, the specific preparation steps comprising:
[0030] S1, grinding the above-mentioned negative electrode-free sodium-based dual-ion battery positive electrode material for 1-2 hours, and then preparing a slurry with a solvent of N-methylpyrrolidone (NMP), and the slurry viscosity is 3000-5000 cps;
[0031] S2, uniformly coating the above slurry on the current collector with a surface loading of ≥8 mg / cm2, and vacuum drying at 60-120°C for 12-36h to obtain a negative electrode-free sodium-based dual-ion battery positive electrode.
[0032] A negative electrode-free sodium-based dual-ion battery comprises the positive electrode.
[0033] No negative electrode means that the negative electrode only has a current collector but no active material, and the negative electrode current collector is a carbon-coated aluminum foil.
[0034] The negative electrode-free sodium-based dual-ion battery also includes a diaphragm and an electrolyte, wherein the diaphragm is a glass fiber diaphragm; the electrolyte in the electrolyte is one or a combination of sodium perchlorate, sodium tetrafluoroborate, sodium hexafluorophosphate, sodium trifluoromethylsulfonate, sodium nitrate, sodium bis(trifluoromethylsulfonyl)imide, sodium bisfluoromethylsulfonylimide, and sodium difluorooxalatoborate; the organic solvent in the electrolyte is one or a combination of tetraethylene glycol dimethyl ether, ethylene glycol dimethyl ether, triethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,3-dioxolane, tetrahydrofuran, tetrahydro-2-methylfuran, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene carbonate, methyl propyl carbonate, 1,4-butyrolactone, butylene carbonate, dibutyl carbonate, methyl butyl carbonate, methyl acetate, methyl formate, methyl propionate, methyl butyrate, ethyl propionate, butyl propionate, and butyl butyrate. The electrolyte and organic solvent in the above electrolyte are commonly used in the industry, and the selection of electrolyte and organic solvent is based on the positive electrode redox platform potential. The selection of electrolyte and organic solvent is not within the scope of protection of the present invention. The present invention aims to study the effect of cation-embedded sodium-poor positive electrode on the coulombic efficiency and discharge specific capacity of negative electrode-free sodium-based dual-ion battery under the same electrolyte and organic solvent conditions.
[0035] Example 1
[0036] Preparation of negative electrode-free sodium-based dual-ion battery positive electrode: by weight percentage, 72% anion-intercalated positive electrode graphite and 8% cation-intercalated sodium-poor positive electrode perylene tetracarboxylic dianhydride (PTCDA), 10% conductive agent conductive carbon black (Super-p), 10% binder polyvinylidene fluoride (PVDF); the above formula was mixed and ground for 1 h, and a slurry was prepared using solvent N-methylpyrrolidone (NMP). The slurry had a viscosity of about 4000 cps, and the slurry was evenly coated on the current collector with a surface loading of ≥8 mg / cm 2 , and vacuum dried at 80 °C for 24 h to obtain the cathode for the double ion battery without negative electrode.
[0037] Electrolyte preparation: 1 M sodium hexafluorophosphate, a mixed solvent of EC:DEC with a volume ratio of 1:1 as solvent, and 5 vol% FEC additive.
[0038] Diaphragm preparation: Use a cutting machine to cut the glass fiber diaphragm to prepare a disc with a diameter of 19 mm as a negative electrode-free sodium-based dual-ion battery diaphragm, and dry it for later use.
[0039] Negative electrode preparation: Use a cutting machine to cut the carbon-coated aluminum foil to prepare a disc with a diameter of 19 mm, which is used as a negative electrode-free sodium-based dual-ion battery separator and is dried for later use.
[0040] A negative electrode-free sodium-based dual-ion battery assembly: In a glove box protected by a high-purity argon atmosphere, the positive and negative electrodes and separators are stacked in sequence, and electrolyte is dripped and infiltrated to finally assemble a 2032-type button battery.
[0041] Figure 1 The scanning electron microscope images of the carbon-coated aluminum foil current collector negative electrode before cycling (a) and after the first cycle of Example 1 (b) are shown. Figure 1 It can be seen that both of them show a state of particle aggregation, and the latter has no obvious change in morphology compared with the former. The first cycle charge and discharge curve of Example 1 is as follows: Figure 2 As shown, from Figure 2 It can be seen that the coulombic efficiency is 40.9% and the discharge capacity is: 31.02 mAh g -1 .
[0042] Example 2
[0043] The cathode of the sodium-based dual-ion battery without negative electrode comprises, by weight percentage, 72% of anion-embedded cathode polytriphenylamine and 8% of cation-embedded sodium-poor cathode PTCDA, 10% of conductive agent conductive carbon black (Super-p), and 10% of binder polyvinylidene fluoride (PVDF); the electrolyte solvent is diethylene glycol dimethyl ether, and the rest is the same as in Example 1.
[0044] Example 2 The cycle stability test results of the negative electrode-free sodium-based dual-ion battery are as follows Figure 3 As shown in Figure 2, at 0.5 C, the first cycle discharge capacity is 99.99 mAh g -1 The coulombic efficiency is 75.06%, and the discharge capacity at the 100th cycle is 78.37 mAhg -1 The coulombic efficiency is 99.13% and the specific capacity retention rate is 78.37%.
[0045] Example 3
[0046] The cathode of the sodium-based dual-ion battery without negative electrode contains, by weight percentage, 65% of anion-embedded cathode polytriphenylamine and 15% of cation-embedded sodium-poor cathode material sodium titanium phosphate, and the rest is the same as in Example 1.
[0047] The first cycle charge and discharge curve of the negative electrode-free sodium-based dual-ion battery prepared in Example 3 is as follows: Figure 4 As shown, the coulombic efficiency is 75.56% and the discharge capacity is 91.8 mAh g -1 .
[0048] Example 4
[0049] The cathode of the sodium-based dual-ion battery without negative electrode contains, by weight percentage, 75% of polytriphenylamine, an anion-embedded cathode material, and 5% of sodium titanium phosphate, a cation-embedded sodium-poor cathode material. The rest is the same as in Example 1.
[0050] The first cycle charge and discharge curve of the negative electrode-free sodium-based dual-ion battery prepared in Example 4 is as follows: Figure 5 As shown, the Coulomb efficiency is 67.2% and the discharge capacity is 82.8 mAh g -1 .
[0051] Comparative Example 1
[0052] The difference from Example 1 is that 72% of the anion-intercalated positive electrode graphite and 8% of the cation-intercalated sodium-poor positive electrode PTCDA are replaced with 80% of the anion-intercalated positive electrode graphite.
[0053] Comparative Example 1 The first cycle charge and discharge curve is as follows Figure 7 As shown, the coulombic efficiency is 28.4% and the discharge capacity is: 28.4 mAhg -1 .
[0054] Figure 6 This is a scanning electron microscope image of the carbon-coated aluminum foil current collector negative electrode after the first cycle of Comparative Example 1. Figure 6 It can be seen that the negative electrode surface of the negative electrode-free sodium-based dual-ion battery prepared in Comparative Example 1 exhibits a moss-like continuous morphology after the first cycle, which is quite different from the carbon particle aggregation state of the uncycled carbon-coated aluminum foil current collector negative electrode, and the moss-like continuous morphology is caused by excessive Na deposition. The above results show that the negative electrode-free sodium-based dual-ion battery positive electrode prepared by the present invention can effectively improve or even eliminate the problem of excessive Na metal deposition by utilizing the characteristics of sodium-poor positive electrode materials in discharging and storing sodium.
[0055] Example 1 First cycle charge and discharge curve ( Figure 2 ) and the first cycle charge and discharge curve of comparative example 1 ( Figure 7) By comparison, it can be seen that since the excess Na deposited during charging on the negative electrode side is effectively utilized, the sodium-poor positive electrode material PTCDA can effectively improve the discharge capacity, coulomb efficiency and energy utilization rate of the anion-embedded graphite-based positive electrode. Figure 4 ) and Example 4 ( Figure 5 ) and Comparative Example 2 ( Figure 8 ) electrochemical performance comparison, we can also get the similar conclusion as above, the anion embedded polytriphenylamine-based positive electrode can improve its discharge specific capacity, coulombic efficiency and energy utilization rate through the sodium-poor positive electrode material sodium titanium phosphate.
[0056] Comparative Example 2
[0057] The difference from Comparative Example 1 is that 80% of the anion-embedded positive electrode graphite is replaced by 80% of polytriphenylamine, and diethylene glycol dimethyl ether is used as the electrolyte solvent. The rest is the same as Comparative Example 1.
[0058] Comparative Example 2 The cycle stability test results of the sodium-based dual-ion battery without negative electrode are as follows Figure 8 As shown in Figure 2, at 0.5 C, the first cycle discharge capacity is 74.11 mAh g -1 The coulombic efficiency is 54.74%, and the discharge capacity at the 100th cycle is 41.74 mAhg -1 The coulombic efficiency is 96.48% and the specific capacity retention rate is 56.32%.
[0059] By Example 2 ( Figure 3 ) and Comparative Example 2 ( Figure 8 ) Comparison of the battery cycle stability test results shows that the battery assembled with the anion-embedded polytriphenylamine positive electrode and the cation-embedded sodium-poor positive electrode PTCDA disclosed in the present invention has a 39.15% increase in specific capacity retention after 100 cycles, and a net increase in specific capacity of 87.75%. This result can prove that the use of sodium-poor positive electrode materials can improve or even eliminate the problem of excessive Na metal deposition, reduce the side reaction of rich Na metal and electrolyte, and improve the coulombic efficiency of the anion-embedded positive electrode, thereby achieving a long cycle life of a negative electrode-free sodium-based dual-ion battery.
[0060] The technical effects that the present invention can achieve are:
[0061] The present invention effectively improves or even eliminates the problem of metal Na accumulation in the negative electrode of the sodium-based dual-ion battery without a negative electrode. This can be demonstrated by comparing the microscopic morphology SEM photos of Example 1 and Comparative Example 1.
[0062] The present invention significantly improves the electrochemical performance of the first cycle coulombic efficiency and cycle life of the negative electrode-free sodium-based dual-ion battery. Figure 3) Compared with comparative example 2, the coulombic efficiency increased from 54.74% to 75.06%, the specific capacity retention rate after 100 cycles increased by 39.15%, and the specific capacity increased by 87.75%.
[0063] The above is only a preferred embodiment of the present invention. It should be pointed out that for those skilled in the art, several changes and improvements can be made without departing from the overall concept of the present invention, which should also be regarded as the scope of protection of the present invention.
Claims
1. A positive electrode for a sodium-based dual-ion battery without a negative electrode, characterized in that: The invention comprises, by weight percentage, 65-75% of anion-embedded positive electrode, 15-5% of cation-embedded sodium-poor positive electrode material, 10% of conductive agent and 10% of binder, wherein the anion-embedded positive electrode is one of graphite and polytriphenylamine; the cation-embedded sodium-poor positive electrode material is one of sodium titanium phosphate and perylenetetracarboxylic dianhydride.
2. The cathode of the sodium-based dual-ion battery without negative electrode according to claim 1, characterized in that: The conductive agent is conductive carbon black; the binder is polyvinylidene fluoride.
3. A method for preparing a positive electrode of a sodium-based dual-ion battery without a negative electrode, characterized in that: The specific preparation steps include: S1, grinding the negative electrode-free sodium-based dual-ion battery positive electrode material according to claim 1 or 2 for 1-2 hours, and then preparing a slurry with a solvent of N-methylpyrrolidone, and the slurry viscosity is 3000-5000 cps; S2, evenly apply the above slurry on the current collector, with a surface loading of ≥8 mg / cm 2 , and vacuum dried at 60-120 ℃ for 12-36 h.
4. A negative electrode-free sodium-based dual-ion battery, characterized in that: A positive electrode for a sodium-based dual-ion battery without a negative electrode as described in claim 1 or 2.
5. The negative electrode-free sodium-based dual-ion battery according to claim 4, characterized in that: No negative electrode means that the negative electrode only has a current collector but no active material, and the negative electrode current collector is a carbon-coated aluminum foil.